Geomagnetic ground survey in Slovakia for the 2007.5 epoch - DOLINSKÝ, Peter; VALACH, Fridrich; VÁCZYOVÁ, Magdaléna; HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2009)
New  geomagnetic ground  survey  was  carried  out in  years  2006–2008.   The survey  was accomplished under  fair geomagnetic-activity conditions during  the minimum phase  of a solar  activity  cycle No. 23.  The  measurements  of the geomagnetic ﬁeld were reduced  to the 2007.5 epoch using magnetograms of the Hurbanovo Geomagnetic Obser- vatory. The distribution of the geomagnetic ﬁeld over the territory of Slovakia is presented in the  paper  in terms  of isoline contour maps  of the  northern, eastern, and  vertical geomagnetic components  together  with  the total magnetic intensity.  The  map  of magnetic declination is added  because  of its practical importance. In addition, the maps  of the normal geomagnetic ﬁeld represented by ﬁrst-degree polynomial model  are shown  here.  The maps  are  also  available on the web site http://www.geomag.sk/GMP/MagnMapsSk. Data of some nearby repeat stations in the  adjoining countries were also employed  in order  to create  the  isoline contour maps.